Dynamic Social Psychology in Group Interaction Patterns and Their Influence on Conformity and Identification - Miriro, Ropafadzo; Farai, Tinashe; Nyasha, Chipo (Journal Social Humanity Perspective, 2024)
The proposed study explores the relations and interactions of social psychology when applied to groups of people, that is, how people behave conformingly and how they identify with their groups. The aim was to investigate how people are converging with the norms of groups, and how individuals are examining the effect that identification with groups has on convergence. This research was conducted under the form of a quantitative correlational study using a structured questionnaire, which was applied to 320 students in a university actively working on group based academic and extracurricular activities. Verified measures addressed conformity tendency and group identification, and interaction pattern, whereas correlation, regression, and ANOVA tests were used to gauge correlation, difference between demographical and disciplinary groups. The results have indicated the existence of a strong positive correlation between group identification to conductive behavior as well as interaction patterns that also became significant predictors. This set of variables combined contributed to 42 percent of variance in conformity which shows that psychology and group level forces play a significant role in the conformity. Disciplinary differences still indicated that conformity is not universal but it varies depending on the circumstances. It is interesting to note that gender and age were not significant predictors indicating that conformity is more of a social identity process than a demographic factor. These findings have great theoretical and practical implications. They are further sharpening the Social Identity Theory due to the active process of negotiation of belonging and autonomy within modern group dynamics, including in digital and hybrid settings. Practically, the paper provides organizational leaders, educators and policymakers with the information about how they can influence constructive identification and reduce the occurrence risks of over conformity. The positioning of conformity in the context of a changing social and cultural environment develops the body of knowledge in the field of study and also offers applicable information that can be used in managing collective behaviors.